FREQUENCY OF SEVERE MITRAL STENOSIS IN YOUNG FEMALE PATIENTS HAVING PURE MITRAL STENOSIS SECONDARY TO RHEUMATIC HEART DISEASE - Ahmad, Shakeel; Hayat, Umar; Naz, Humera (Journal of Ayub Medical College Abbottabad, 2010)
Background: High morbidity and mortality due to Rheumatic heart disease (RHD) associated with females is mainly because of late diagnosis on one hand and socioeconomic reasons on the other hand. Poor referral to tertiary care centres leads to delayed diagnosis which results in complications. The objectives of this cross-sectional descriptive study was to assess the frequency of severe mitral stenosis in woman of child bearing age, having pure mitral stenosis (MS) secondary to rheumatic heart disease. Methods: Two hundred and fifty women of child bearing age with RHD were enrolled in the study using consecutive non-probability sampling technique. Out of these 250 patients, cases of pure MS were selected. Patients with associated mitral regurgitation and aortic valve disease were excluded. After admission, assessment of mitral valve stenosis was done with 2D colour Doppler echocardiography. Results: Out of 250 consecutive patients of rheumatic carditis, 110 (44%) patients had pure mitral valve stenosis, 85 (34%) had stenosis with mitral regurgitation and 55 (22%) patients had both mitral and aortic valve problem of varying severity. Among 110 patients with pure mitral valve stenosis, 48 (43.6%) had severe mitral valve stenosis. Severe mitral valve gradient (MVG) and high pulmonary artery pressure (PAP) was observed in 66 (60%) and 49 (44.5%) of the patients respectively. Conclusion: This high frequency can be linked to lack of early detection of the disease at primary level, poor management of throat infections and poor rheumatic fever prophylaxis at community level. Keywords: Rheumatic heart disease, mitral stenosis, mitral valve gradient, pulmonary artery pressure, primary health centre